Bending fatigue failure mechanisms of twill fabric E-Glass/Epoxy composite. (April 2015) - Beyene, Alem Tekalign; Belingardi, Giovanni
Abstract: Composite materials exhibit very complex failure mechanisms because of their heterogeneous property leads the formation of different stress levels within the material and results various combinations of damage. The objective of this research is a contribution to physical understanding of composite failure mechanism under bending fatigue loading, as a physical understanding of composite failure mechanism is crucial step for developing both theoretical and numerical models. To investigate the fatigue damaging mechanism and the resulting material strength deterioration of a particular composite material, four-point flexural quasi-static and displacement-controlled fatigue tests have been performed. The analysis methodology relies on interrupted flexural fatigue tests. The damage formation and propagation was continuously monitored through the decrement of bending moment during cycling. This leads to a characteristic history curve that can be subdivided into three stage, namely initial, intermediate and final. Each of them has specific trend in stiffness degradation. Through microscope and SEM image analysis of the pre-cycled specimens, four different subsequent failure modes and mechanisms of the targeted material are identified at different stages of component life. A correlation between the trend of the bending moment time history and the sequence of the different failure modes is established.